Experiences of classroom teachers on the use of hands-on material and educational software in math education - Kukey, Ebru; Gunes, Habibe; Genc, Zulfu (Birlesik Dunya Yenilik Arastirma ve Yayıncilik Merkezi, 2019)
One of the most common challenges expressed by classroom teachers in mathematics teaching and in the literature is the concretisation of abstract concepts in teaching basic subjects. Lego MoreToMath is a training set focusing on the mathematical lesson gains of elementary school first and second grade students. The aim of this study is to enable teachers to experience Lego MoreToMath, which is a combination of building toys and educational software, by using the summer camp as a TÜBiTAK 4005 project. The study was conducted with 25 classroom teachers and their opinions were taken during the 1-week training process. Data were collected through observation and interview techniques by keeping field notes. In the study, a descriptive analysis approach was used as the data analysis technique. The teachers stated that using a different approach in mathematics teaching developed them professionally and they wanted to use such approaches in their lessons. © 2019 SciencePark Research, Organization & Counseling. All rights reserved.
Keywords: Educational software; Fluency; Hands-On material; Problem-Solving; Reasoning